2018
DOI: 10.1103/physrevlett.121.046101
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Free-Space Light Transport at Nonlinear Metasurfaces

Abstract: Asymmetric light transport has significantly contributed to fundamental science and revolutionized advanced technology in various aspects such as unidirectional photonic devices, optical diodes and isolators. While metasurfaces mold wavefronts at will with an ultrathin flat optical element, asymmetric transport of light cannot be fundamentally achieved by any linear system including linear metasurfaces. We report asymmetric transport of free-space light at nonlinear metasurfaces upon transmission and reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…Moreover, there have been few successful attempts to obtain asymmetrical transmission based on a coupled multiple-microcavity system with balanced gain and loss, i.e., parity-time symmetry [ 19 , 20 ]. Most recent scientific efforts in this field have been oriented towards exploitation of artificially-created structures, the so-called metamaterials [ 21 , 22 , 23 , 24 , 25 ]. Until now, it has been demonstrated that a complex triple-helix metamaterial structure may provide magnetic-free optical isolation within a broad spectral range [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there have been few successful attempts to obtain asymmetrical transmission based on a coupled multiple-microcavity system with balanced gain and loss, i.e., parity-time symmetry [ 19 , 20 ]. Most recent scientific efforts in this field have been oriented towards exploitation of artificially-created structures, the so-called metamaterials [ 21 , 22 , 23 , 24 , 25 ]. Until now, it has been demonstrated that a complex triple-helix metamaterial structure may provide magnetic-free optical isolation within a broad spectral range [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been discovered that the metasurface can effectively manipulate the polarization state of light [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. For the circularly polarized (CP) incidence, a rotation-induced geometrical phase, known as the Pancharatnam-Berry (P-B) phase, is generated by rotating the anisotropic building elements [25][26][27][28][29][30][31][32][33][34][35]. Yet, this phase modulation on LCP and RCP is strongly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed the emergence of "metasurfaces" based on the generalized Snell's law (GSL), [1] which provides an unprecedented way to engineering phase, amplitude, and polarization of wave and designing advanced functional devices. In electromagnetic-wave systems, [2][3][4][5][6][7][8] by introducing desirable polarization, phase, and amplitude profiles of metasurfaces, anomalous refractions or reflections have been achieved, [9,10] and complex wavefront of single or multiple subwavelength scatterers, in which the coupling effect between adjacent unit cells plays an important role in diffraction modulations. Different from conventional gratings that usually possess several diffraction orders, the metagratings can suppress undesired diffraction orders and reroute all waves towards a single propagation direction, resulting in anomalous refraction or reflection with high efficiency.…”
Section: Introductionmentioning
confidence: 99%